1995
DOI: 10.1159/000119195
|View full text |Cite
|
Sign up to set email alerts
|

ECG Activity in the Sleep of Insomniac Patients under the Influence of Lormetazepam and Zopiclone

Abstract: The influence of the benzodiazepine hypnotic lormetazepam (1 mg) and the cyclopyrrolone hypnotic zopiclone (7.5 mg) on heart rate activity was studied in 16 elderly insomniacs in a placebo-controlled, randomised, 3-fold crossover trial. After digital preprocessing of the ECG, QRS complexes were automatically recognised by a detection technique based on adaptative thresholds. Both R-R periodicity and heart rate variability were analysed as a function of sleep stages and time of night. Under placebo, heart rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In fact the oral benzodiazepines, used for the treatment of insomnia and anxiety in community-dwelling subjects, unlike the intravenous ones [171], [172] have mostly been reported to have no effect on HRV [165], [167], [169], with some exception [166], [168]. Moreover, a recent and larger study in patients with schizophrenia [154], making no distinction between routes of administration, demonstrated that daily benzodiazepine dose was not associated with frequency-domain measures of HRV.…”
Section: Discussionmentioning
confidence: 99%
“…In fact the oral benzodiazepines, used for the treatment of insomnia and anxiety in community-dwelling subjects, unlike the intravenous ones [171], [172] have mostly been reported to have no effect on HRV [165], [167], [169], with some exception [166], [168]. Moreover, a recent and larger study in patients with schizophrenia [154], making no distinction between routes of administration, demonstrated that daily benzodiazepine dose was not associated with frequency-domain measures of HRV.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, 34 studies were identified that met the inclusion criteria for this review. Twenty six observational studies ([ 8 , 11 13 , 47 , 53 , 57 , 59 63 , 65 , 66 , 68 73 , 82 87 ]) and eight interventional studies ([ 64 , 67 , 74 78 , 88 ]). Study details such as diagnostic criteria, demographics, number of participants, insomnia severity, and type of intervention are presented in Tables 4 and 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Jobert et al [ 88 ] compared the effect of pharmacologic treatment (benzodiazepine hypnotic lormetazepam and cyclopyrrolone hypnotic zopiclone) on HR activity in elderly patients with a diagnosis of psychophysiological insomnia. Their results showed that the relation between sleep and HR remained constant under the influence of a single dose of lormetazepam or zopiclone.…”
Section: Resultsmentioning
confidence: 99%
“…12,19 Zopiclone adds no significant influence in ventilation, except a transient increase of breathing frequency after 5 min of injection (7.5 mg). 21 Its affect on electrocardiogram activity, 22 heart rate, and blood pressure 21,23 was also very slight in the treating dose of 7.5 mg. Therefore, it seems less likely that zopiclone would add a significant effect on PTT in patients with obstructive sleep apnea.…”
Section: Discussionmentioning
confidence: 98%